MINAT CHURN PELANGGAN INDOSAT DI INDONESIA - Pertiwi, Resty Wahyu; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2015)
This study developes a model with phone network disquality, lack of internet access speed as independent variables and dissatisfaction as intervening variable, then affecting churn intention.The number of samples in this study were 500 respondents. Questionaires were distributed to Indosat’s users from February 2015 until April 2015, using a purposive sampling method. Technical analysis employed AMRA.The results showed that two of the independent variables directly influenced customer disatisfactio and affected churn intention. The highest value variable influencing customer dissatisfaction is the factor lack of internet access speed. Supported by previous studies, customer disatisfaction has positive relation and significantly mediates the effect of independents variables to engage churn intention.